Changes in beta cell function during the proximate post‐diagnosis period in persons with type 1 diabetes. Issue 4 (27th February 2015) - DiMeglio, Linda A; Cheng, Peiyao; Beck, Roy W; Kollman, Craig; Ruedy, Katrina J; Slover, Robert; Aye, Tandy; Weinzimer, Stuart A; Bremer, Andrew A; Buckingham, Bruce
Abstract : Objective: Prior studies examining beta‐cell preservation in type 1 diabetes have predominantly assessed stimulated C‐peptide concentrations approximately 10 wk after diagnosis. We examined whether earlier assessments might aid in prediction of beta cell function over time. Methods: Using data from a multi‐center randomized trial assessing the effect of intensive diabetes management initiated within 1 wk of diagnosis, we assessed which clinical factors predicted 90‐min mixed‐meal tolerance test (MMTT) stimulated C‐peptide values obtained 2 and 6 wk after diagnosis. We also studied associations of these factors with C‐peptide values at 1‐ and 2‐year post‐diagnosis. Data from intervention and control groups were pooled. Results: Among 67 study participants (mean age 13.3 ± 5.7 yr, range 7.8–45.7 yr) in multivariable analyses, C‐peptide increased from baseline to 2 wks and then 6 wk. C‐peptide levels at these times were significantly correlated with 1‐ and 2‐yr C‐peptide concentrations (all p < 0.001), with the strongest observed associations between 6‐wk C‐peptide and the 1‐ and 2‐yr values (r = 0.66 and r = 0.61, respectively). In multivariable analyses, greater baseline and 6‐wk C‐peptide, and older age independently predicted greater 1‐ and 2‐yr C‐peptide concentrations. Conclusions: C‐peptide assessments close to diagnosis were predictive of subsequent C‐peptide production. Our data demonstrate a clear increase in C‐peptide over the initial 6 wk after diabetes diagnosis followed by a plateau. Our data do not suggest that MMTT assessments performed closer to diagnosis than 6 wk would improve prediction of subsequent residual beta cell function.